2013
DOI: 10.1016/j.jaad.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Scleromyxedema: A multicenter study of characteristics, comorbidities, course, and therapy in 30 patients

Abstract: Our study confirms that scleromyxedema is a chronic and unpredictable disease with severe systemic manifestations leading to a guarded prognosis. There is no specific definitive treatment. Our data support the contention that intravenous immunoglobulin is a relatively effective and safe treatment. The response is not permanent and maintenance infusions are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
307
2
30

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(347 citation statements)
references
References 26 publications
8
307
2
30
Order By: Relevance
“…A multicenter study of 30 patients with scleromyxedema reported that the mean age of presentation was 59 years, and the average time from onset of this disease to diagnosis was nine months. 2 The pathophysiology of scleromyxedema remains unclear. It has been described that fibroblasts of patients with this disease synthesize more hyaluronic acid than normal and, subsequently, more mucin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicenter study of 30 patients with scleromyxedema reported that the mean age of presentation was 59 years, and the average time from onset of this disease to diagnosis was nine months. 2 The pathophysiology of scleromyxedema remains unclear. It has been described that fibroblasts of patients with this disease synthesize more hyaluronic acid than normal and, subsequently, more mucin.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports and case series have demonstrated improvement of cutaneous and extracutaneous signs and symptoms of scleromyxedema during IV Ig therapy, and appears to be well tolerated. 2,10 Second line treatment is thalidomide (or lenalidomide) and systemic glucocorticoids. This treatment can be given alone or in combination with IV Ig.…”
Section: Discussionmentioning
confidence: 99%
“…İVİG tedavisi pahalı olmasına rağmen etkin ve yan etkilerinin daha az olması nedeniyle literatürde sık kullanılmıştır. Fakat etkisinin kalıcı olmaması ve tekrarlayan tedavilere ihtiyaç duyulması maliyeti artırmaktadır 6,7 . Temini kolay bir ilaç olan retinoid; fibroblast proliferasyonunu baskılayarak dolayısıyla müsin salınımını engelleyerek etki gösterir 12 .…”
Section: Olgu Sunumuunclassified
“…Metilprednizolona başlandıktan sonra 1 hafta içerisinde lezyon boyutunda küçülme görülürken, 3 aylık periyod içerisinde steroide tamamen yanıt alındı ve 6 aydır da ilaçsız izlenip halen nüks görülmedi. Buna karşın daha önceki yayınlanan bazı olgu serilerinde de steroide yanıt alınamadığı bildirilmiştir 7,14 . Bununla birlikte literatürde kendiliğinde gerilemenin de 15 yıl sonra görülebileceği bildirilmiştir 1 .…”
Section: Olgu Sunumuunclassified
“…Şimdiye kadar bildirilen az sayıda olguda özefagus, mide, karaciğer, over, pankreas, mesane karsinomları tespit edilmiştir 4 . Ayrıca myeloid lösemi ve Hodgkin lenfoma da bulunabilir 5 . Sklerömiksödem, paraneoplastik özelliklerin yanında, sistemik tutulum gösterebilmesi nedeniyle de önem taşır.…”
Section: Sklerömiksödemunclassified